2015
DOI: 10.4067/s0717-95022015000100044
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Tribulus terrestris Hydroalcoholic Extract Against Cisplatin­Induced Apoptosis on Testis in Mice

Abstract: SUMMARY:Cisplatin is an anti-cancer drug used in chemotherapy. One of the limiting side effects of cisplatin is decreasing genital gland function, azoospermia and oligospermia. Tribulus terrestris (TT) has been used as an aphrodisiac. The present study amid to investigate protective effect of TT hydroalcoholic extract against cisplatin-induced apoptosis on testis in mice. Male adult mice (n=30) were divided into control and 4 experimental groups (n=6). Control group received saline, first experimental group re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These data were similar to other studies (Shenoy & Ramesh;Suthagar et al, 2009;Kianifard et al, 2011). The weight gain in diabetic rats that were treated with T. terrestris confirmed Keshtmand et al (2015). The study showed that weight loss caused by diabetes can be compensated by T. terrestris extract first time.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…These data were similar to other studies (Shenoy & Ramesh;Suthagar et al, 2009;Kianifard et al, 2011). The weight gain in diabetic rats that were treated with T. terrestris confirmed Keshtmand et al (2015). The study showed that weight loss caused by diabetes can be compensated by T. terrestris extract first time.…”
Section: Discussionsupporting
confidence: 52%
“…The serum samples were then kept in deep freezer (-18 ºC) until measurement of testosterone hormone by ELISA method. Also, the testes were separated and weighed separately and then preserved in neutral buffered formalin 10 % (Keshtmand et al, 2015;Moradi et al, 2015).…”
Section: Preparation Of Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, administration of T. terrestris extract could significantly inhibit the gluconeogenesis and influence glycometabolism on normal mice and also reduces the level of triglyceride and the content of cholesterol in the plasma (Keshtmand et al, 2015). In previous works we showed the efficacy of T. terrestris extract on kidney injury induced by cisplatin and also side effects of diabetes on testis, sperm parameters and sexual hormones (Keshtmand et al, 2014;Keshtmand et al, 2015;Raoofi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Then, fresh fruits of T. terrestris L were dried in shade at room temperature (25±2 ºC) and its extract was obtained through the percolati on method. Extracting method was described previously (Keshtmand et al, 2015). With this method, approximately 200 g of the dry plant specimen was ground and added to 400 mL of 70 % ethanol and were left to macerate at room temperature for 4 h. Then, the tinctured grains were extracted by percolation method and extract concentrated in a vacuum and dried in the flat surface.…”
Section: Methodsmentioning
confidence: 99%